Application of artificial intelligence techniques in the administrative management of higher education institutions: an analysis of their effectiveness in process optimization and strategic decision making (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
This study investigated the effectiveness of artificial intelligence (AI) in the administrative management of higher education institutions. Through the use of surveys and interviews, the perception and acceptance of AI was evaluated, as well as its impact on process optimization and strategic decision making. The results revealed a high acceptance of AI in administrative management, supporting its effectiveness in process improvement and decision making. Significant positive correlations were found between the effectiveness of AI and the quality of administrative services, productivity and cost reduction. These findings highlight the transformative potential of AI in the administrative management of higher education institutions, providing a solid foundation for the implementation of AI-based strategies and the improvement of efficiency and effectiveness in administrative management.